1927 Ind. Acts 469, Operation of Machine Guns, Discharge of Bombs — Offense and Penalty:, ch. 156, § 2 - (:unkn) unknown (General Publisher, 1927)
Prohibited discharging a machine gun or bomb. Punishable by imprisonment for 2-10 years.
--
Keywords: DISCHARGE